Plasma biomarkers of inflammation, coagulation, and brain injury as predictors of delirium duration in older hospitalized patients. - J Brennan McNeil; Christopher G Hughes; Timothy Girard; Lorraine B Ware; E Wesley Ely; Rameela Chandrasekhar; Jin H Han (PLoS ONE)
Background Delirium's pathophysiology is poorly understood. We sought to determine if plasma biomarkers of inflammation, coagulation, endothelial activation, and blood brain barrier (BBB) injury were associated with emergency department (ED) delirium duration. Methods We enrolled hospitalized patients who were 65 years or older from the ED. Plasma biomarkers of inflammation (interleukin-6 [IL-6], IL-8, soluble tumor necrosis factor receptor I [sTNFRI]), coagulation (Protein C), endothelial activation (plasminogen activating inhibitor-1 [PAI-1]), and BBB injury (S100B) at were measured using blood obtained at enrollment. The dependent variable was ED delirium duration which was determined by the Brief Confusion Assessment Method assessed in the ED and hospitalization. Proportional odds logistic regression analyses were performed adjusted for relevant confounders and allowing for interaction by baseline dementia status. Results A total of 156 patients were enrolled. IL-6 (POR = 1.59, 95%CI: 1.09-2.32) and PAI-1 (POR = 2.96, 95%CI: 1.48 to 6.85) were independently associated with more prominent ED delirium duration in subjects without dementia only. No significant associations between IL-8, Protein C, sTNRFI, and S100B and ED delirium duration were observed. Conclusions Plasma Biomarkers of systemic inflammation and endothelial activation are associated with ED delirium duration in older ED patients without dementia.